PSYCHOLOGICAL FACTORS OF ENHANCING CREATIVE MOTIVATION IN FUTURE MUSIC EDUCATORS (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the psychological mechanisms of developing creative thinking in music education. It highlights the key processes—idea generation, metacognition, and the creation of a supportive pedagogical environment—that enhance creative activity among future music teachers. The study emphasizes that creativity in music teaching emerges through emotional awareness, reflective thinking, and freedom of expression, forming the foundation for innovative and student-centered learning.